Improving Business Performance: The Influence of Entrepreneurial Characteristics and Digital Literacy through Marketing Capability - Desva Novianti; Marwan Marwan (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to analyze the effect of entrepreneurial characteristics and digital literacy on the performance of culinary small businesses through marketing capabilities as mediation in Padang City. The existence of MSMEs is very important in creating economic stability, especially in the culinary sector, which is one of the main pillars of the regional economy. The method used in this research is quantitative with a survey approach, where the population studied includes all culinary MSME players in Padang City. The sample taken amounted to 170 culinary small business owners registered in various associations and entrepreneurial communities. The results show that entrepreneurial characteristics have a positive and significant influence on marketability. These entrepreneurial characteristics include innovative attitude, risk-taking courage, and skills in managing the business, which increase marketing effectiveness. Marketing capability is proven to have a positive and significant effect on business performance, because the right marketing strategy can increase sales and business competitiveness. Meanwhile, digital literacy has a positive influence on marketing ability and business performance, but the effect is not significant. This suggests that although digital literacy is important, the implementation of technology in marketing and business performance has not been fully optimized. This study also confirms that entrepreneurial characteristics have a positive influence on business performance through marketing ability as a mediator, while digital literacy does not have a significant influence on business performance through marketing ability as a mediator